Billet distribution and initial establishment of sugarcane due to the planting shifts - Junior, Wilson de Almeida Orlando; Paixão, Carla Segatto Strini; Voltarelli, Murilo Aparecido [UNESP]; da Silva Girio, Lucas Augusto; da Silva, Rouverson Pereira; Fernandes, Haroldo Carlos (Southern Cross Publishing, 2018)
The increased production of sugarcane becomes increasingly dependent on mechanization mainly planting to achieve better performance, quality and cost reduction of operation. This study aimed to evaluate the mechanized planting operation of sugarcane in day and night shifts, through evaluations in the distribution of billets and early crop establishment. The mechanized planting was performed using a tractor-planter set with the chopped cane planter with two rows of fertilizer shanks spaced by 1.5 m. A randomized blocks experimental design with 40 replications was implemented in sub-split plot scheme, considering the shifts (day and night) as main treatments, grooves (right and left) as subplots. Spacing (distribution of billets, viable buds, percentage of viable buds and consumption of buds) and time (tillering and failures in sprouting) were considered as sub-sub-plots. The results showed that the shifts had no influence on the mechanical planting operation of sugarcane neither on the quality of distribution of buds in the furrows. The initial crop establishment presented greater tillering values at 30, 60 and 120 days after planting in day shift for the right furrows, as compared to night shift because of the variability in the production environment.
Keywords: mechanization; Operating shifts; Operation quality; Planter; Saccharum spp